Measures Implemented in Uzbek Industry and Their Results (1925 - 1941) - Bekzod Mamatkulov (Genius Journals, 2022)
This article provides a scientific analysis of the implementation of industrialization policy in Uzbekistan and its consequences (1925 - 1941).
Keywords: Heavy industry; knitwear; chemical industry; national economy